The impact of advertising on the circular economy of fashion on consumers' acceptance of reused and recycled fashion - Al-Ghamdi, Suad Abdullah; Al-Dabbagh, Maha Abdullah (Journal of Humanities & Social Sciences, 2023)
This research aims to provide a comprehensive understanding of the circular economy concept in the fashion industry, including its principles, benefits, and challenges,  investigate the role and impact of promotional advertising on consumer awareness and acceptance of circular fashion practices , assess the level of consumer awareness and acceptance of the circular economy of fashion in relation to recycled and reused fashion products, and  suggest strategies and recommendations for industry and institutions to promote sustainable practices and increase consumer adoption of circular fashion. The paper applied the analytical descriptive approach.The study population consisted of 56 female university students. The sample was recruited through social media channels. A questionnaire was designed to gather information in three key areas: demographic data, attitudes towards advertising, and the impact of advertising on the circular economy.Survey results revealed that only 13% of the participants were aware of the circular economy in fashion. Email and WhatsApp were the main channels for accessing the ads. The ads had clear titles and objectives, and effective use of colours, according to 96% and 82% of respondents, respectively. The clarity and alignment of the message with values were less convincing, with only 69% agreeing. The ads were comfortable and not intrusive for 99% of respondents, resulting in an overall attraction rate of 89%. The ads could be improved by enhancing the message clarity and value alignment. The ad raised the awareness of the circular economy in fashion for 98% of respondents. Nearly 99% of respondents wanted to support and encourage the circular economy. There was a high acceptance for recycled fashion (90%), but a lower interest in buying used clothes (75%).
Keywords: Advertising; Circular economy of fashion; circular economy